Epigenetic modifications in the accumulation and function of myeloid-derived suppressor cells - Xu, Liangjie; Zhou, Cuicui; Liang, Yi; Fan, Tinpan; Zhang, Fen; Chen, Xinxin; Yuan, Wei (Frontiers in Immunology, 2022)
Myeloid-derived suppressor cells (MDSCs) are key players under various pathologic conditions, such as cancer. Epigenetic modifications such as DNA methylation, RNA-mediated processes, and histone modification can alter gene transcription, and thus regulating pathological process. Studies have shown that epigenetic modification contributes to the accumulation and function of MDSCs. This review summarizes the crosstalk between the epigenetic alterations and MDSCs functions, and briefly introduces how the accumulation and function of MDSCs caused by epigenetic modification impact on the disease development, which represents as a promising therapeutic strategy for the related disorders.